Corporate sustainability performance and profitability: The moderating role of liquidity and stock price volatility - evidence from Jordan - Rana Taha; Ahmed Al-Omush; Munther Al-Nimer (Cogent Business & Management, 2023)
The study aims to investigate the effect of Corporate Sustainability Performance (CSP) on profitability by examining the moderating role of liquidity and stock price volatility in the Jordanian industrial sector. The sample under study contains 56 Jordanian industrial firms. The study developed an empirical multivariate panel data model to analyze the impact of sustainability (environmental, social and governance) on firm profitability. Further, 38 criteria were utilized in the study to measure CSP to understand whether firms ranked high on sustainability parameters perform better than low-ranked firms. The study reveals a significant positive relationship between CSP and profitability; liquidity and stock price volatility also moderate CSP's effect on the profitability of industrial companies listed on the ASE. Empirical evidence suggests that companies in Jordan should focus on improving CSP activities; to enhance financial performance. The findings could be helpful to investors, senior managers in Jordanian industrial firms, and legislators in Jordan concerning decisions about how to enhance the quality of corporate sustainability and increase the possibility of maximizing the company's profitability. Our methodology and evaluation of corporate sustainability in this context may also be helpful to other researchers on corporate sustainability in developing economies.
Keywords: L25; E31; L16; Q56; 650; profitability; liquidity; ASE; CSP; listed industrial companies; stock price volatility